Neuromuscular Electrical Stimulator as a Diagnostic tool in Obesity- A cross Sectional Study (International Journal of Physiotherapy, 2024)
Background: Obesity is a growing public health concern, particularly in urban areas of India, where it is more prevalent than in rural regions. This study aims to assess the effectiveness of neuromuscular electrical stimulation (NMES) markers in diagnosing Class I and Class II obesity in women.Methods: This cross-sectional study was conducted at the Physiotherapy outpatient department, Madha Hospital, Kovur, Chennai, over 12 weeks. One hundred women aged 20-45 years were included, with 50 in each of the Class I and II obesity groups. Women with Class III obesity or associated co-morbidities were excluded. Anthropometric measurements, such as BMI and skin fold thickness in the abdomen and thigh, along with NMES markers (Surge Faradic Current [SFC] and Interrupted Galvanic Current [IGC]) in the abdomen and thigh, were collected. Data analysis was performed using SPSS version 20. An unpaired t-test was used to compare the NMES markers between the two groups. Correlation analysis between BMI and NMES markers was also conducted. ROC analysis was used to determine the Area under the Curve (AUC) for diagnostic accuracy.Results: There was a significant difference in the NMES markers between Class I and II obese women at P≤0.005. SFC demonstrated a superior diagnostic ability with a higher AUC than IGC at a significance level of P